Experimental, Numerical and Field Approaches to Scour Research - Chiew, Yee-Meng; Lai, Jihn-Sung; Link, Oscar (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents fourteen state-of-the-art research papers prepared by research scientists and engineers around the world. They explore the subject of scour related to bridge piers, monopiles, propellers, turbines, weirs, dams, grade-control structures, and pipelines. Their works are based on three different research methodologies, namely experimental, numerical, and field approaches.